EFFICIENCY ANALYSIS OF THE THREE-PHASE ELECTRIC MOTOR 011P-109B AS THE DRIVE FOR THE LDO PUMP IN THE FUEL OIL PRODUCT UNIT, COMPLEX II, PT KILANG PERTAMINA INTERNASIONAL - Alien Uis Wigati; Bustanul Arifin (Algebra : Jurnal Pendidikan, Sosial dan Sains, 2026)
Induction motors are electrical machines that operate based on electromagnetic principles to convert electrical energy into mechanical energy. In the oil and gas industry, electric motors are widely used for operational processes. This accounts for a large portion of operational costs. At the Fuel Oil Complex II operating unit, the 011P-109B drive motor for the LDO product pump was damaged, so the motor was replaced with one that exceeded the existing specifications, namely from 125HP to 150HP, 111.855 kW, 2 poles, and a frequency of 50 Hz. Research was conducted to test the efficiency of the motor. The method used in this test was a literature review of several publications that comply with national and international standards. Based on efficiency calculations, the 150HP induction motor has superior operational efficiency compared to the 125HP motor, with an average efficiency of 93.63% compared to 93.15%, as well as lower power loss of 4.8kW compared to the 125HP motor, which has a power loss of 5.01kW. The comparison results with the IEC 60034-30-1:2014 standard show that both motors are technically classified in the IE2 (High Efficiency) to IE2+ (Borderline IE3) category.